Numerical Simulation of Mixed Convection Squeezing Flow of a Hybrid Nanofluid Containing Magnetized Ferroparticles in 50%:50% of Ethylene Glycol–Water Mixture Base Fluids Between Two Disks With the Presence of a Non-linear Thermal Radiation Heat Flux - Nisar, Kottakkaran Sooppy; Khan, Umair; Zaib, A.; Khan, Ilyas; Baleanu, Dumitru (Frontiers in Chemistry, 2020)
The colloidal deferment of magnetic nanomaterials and regular liquids are ferroliquids. These fluids have numerous applications in medical science like cell separation, targeting of drug, imaging of magnetic resonance, etc. In addition, the hybrid nanofluid is composed by scattering the magnetic nanomaterial of more than one into the base fluid. It has different scientific applications as heat dissipation, dynamic sealing, damping, etc. Owing to the vast ferrofluids applications, the time-dependent squeezed flow of hybrid ferroliquids under the impact of nonlinear radiation and mixed convection within two disks was explored first time in this analysis. Here, the cobalt and magnetite ferrofluids are considered and scattered them into 50-50% mixture of water-EG (ethylene glycol). The similarity technique is consumed to reduce the leading PDEs into coupled nonlinear ODEs. The transmuted equations together with recommended boundary restrictions are numerically solved via Matlab solver bvp4c. The opposing and assisting flows are considered. The impacts of emerging parameters on fluid velocity and temperature field of hybrid ferroliquids are examined through the different graphical assistance. The results perceived that the opposite trend is scrutinized due to magnetic influence on the temperature and velocity in case of assisting and opposing flows.